Regime of Exception - Quispe Correa, Alfredo (1982)
This article analyzes the constitutional situation in which the effectiveness of the Constitution is partially suspended to address emergencies that threaten State security. The author starts from the premise that traditional constitutions conceived of an unbreakable rule of law. However, reality has shown that there are phenomena that transcend legal and political control, such as anarchy or invasions.  In this context, a Regime of Exception is necessary to allow for quick and appropriate measures to restore order. In this regard, the author discusses the historical background of this regime in the English and French systems, until its inclusion into Peruvian legislation, which adopted both systems, creating a hybrid regime that adjusts to the gravity of the circumstances. Despite being a necessary measure for the government in times of crisis, the author warns of the risk that this regime could be used to cover up despotism. Therefore, he proposes that its use be limited and controlled to prevent abuse and focus on constitutional matters, excluding political or economic motivations that could lead to misuse.